2021
DOI: 10.1002/essoar.10506560.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revealing a High Water Abundance in the Upper Mesosphere of Mars with ACS onboard TGO

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Water vapor vertical distribution has long remained a missing product of Mars' observations. Until recently, the SPICAM infrared spectrometer onboard Mars Express has been the only asset to regularly survey water vapor vertical distribution (Fedorova et al, 2009(Fedorova et al, , 20182021;Maltagliati et al, 2011Maltagliati et al, , 2013 using solar occultation mode, a technique that provides both sensitive (between 1 and 10 parts-per-million in volume, ppmv, in H 2 O volume mixing ratio, vmr) and vertically resolved (3-5 km vertical sampling) measurements. The enhanced presence of water vapor at high altitude during southern summer was already evidenced in some of these works, but SPICAM occultation coverage is hampered by Mars Express highly elliptical orbit, forcing an uneven temporal and latitudinal sampling, as well as by its limited detection capability.…”
Section: Observations Of Water Vapor Vertical Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water vapor vertical distribution has long remained a missing product of Mars' observations. Until recently, the SPICAM infrared spectrometer onboard Mars Express has been the only asset to regularly survey water vapor vertical distribution (Fedorova et al, 2009(Fedorova et al, , 20182021;Maltagliati et al, 2011Maltagliati et al, , 2013 using solar occultation mode, a technique that provides both sensitive (between 1 and 10 parts-per-million in volume, ppmv, in H 2 O volume mixing ratio, vmr) and vertically resolved (3-5 km vertical sampling) measurements. The enhanced presence of water vapor at high altitude during southern summer was already evidenced in some of these works, but SPICAM occultation coverage is hampered by Mars Express highly elliptical orbit, forcing an uneven temporal and latitudinal sampling, as well as by its limited detection capability.…”
Section: Observations Of Water Vapor Vertical Distributionmentioning
confidence: 99%
“…The ACS data used in this study can be found in Belyaev (2021). The data produced by our model can be found in Montmessin (2022).…”
Section: Data Availability Statementmentioning
confidence: 99%